"I Wish I Could Have My Leg": A Qualitative Study on the Experiences of Individuals With Lower Limb Amputation. (March 2022) - Canbolat Seyman, Cigdem; Uzar Ozcetin, Yeter Sinem
Amputation is commonly regarded as a lifesaving procedure. However, the loss of a body part can lead to permanent disability that can impact patients physically, psychologically, and socially. The aim of this study was to describe and understand the perspectives of patients with lower limb amputation (LLA) about their condition. The study uses a descriptive phenomenological design. Data were collected from 12 patients. The researchers conducted interviews using semi-structured questions. MAXQDA was used for qualitative software support in managing the interview data. Data were transcribed. The participants were aged 61.3 ± 10.8 years. Three themes emerged from the qualitative data: (i) losing control over one's own life, (ii) dreams versus the realities of life, and (iii) future perceptions. Most of the participants emphasized that they face undesirable experiences in their post-amputation lives. The findings of the present study provide novel insight into how individuals subjectively experience life after LLA.